Significance of bone marrow immunohistochemical analysis in patients with plasma cell neoplasms - Zh. M. Kozich; V. N. Martinkov; M. Yu. Zhandarov; Zh. N. Pugacheva; N. N. Klimkovich (Онкогематология)
Background. The group of plasma cell neoplasms includes benign and malignant diseases. Sometimes there are difficulties in making a diagnosis. The study of the diagnostic and prognostic significance of immunohistochemical (IHC) markers is of current interest.Aim. To study the significance of IHC markers and histological features of the bone marrow in primary diagnosis in patients with multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS).Materials and methods. The study included 287 patients with plasma cell neoplasms: MGUS (n = 148), MM (n = 139). The observation period was 50 months. All patients have performed an aspiration biopsy and histological examination of the bone marrow with IHC analysis of CD138+, CD56+, CD34+, κ- and λ-chains expression.Results. During the observation period the progression of MGUS to MM was recorded in 8.8 % (n = 13) of cases, the progression of MM was determined in 38.1 % (n = 53) of cases.In patients with MGUS and MM the determined percentage of plasma cells at aspiration biopsy was somewhat lower than at histological examination (p >0.001). Statistically significant differences were determined between the groups MGUS and MM by the type of infiltration (р <0.001). With an increase in the percentage of bone marrow lesions by IHC (<20 % vs. 20–50 % and 20–50 % vs. >50 %), in our study interstitial and diffuse type of lesion with large accumulations was more common compared to the nodular type (p = 0.001).The CD138+ expression (IHC) more than 10 % was associated with a decrease of progression-free survival in patients with MGUS.In MM patients with an interstitial type of bone marrow infiltration and CD138+ over 10 % osteodestructive syndrome was detected by X-ray methods in 82.9 % of cases.Determination of CD56+ and immunoglobulin light chains expression in patients with MM and MGUS indicated an unfavorable prognosis.Resistance to chemotherapy or disease progression in MM patients most often occurred with a combination of IgG and immunoglobulin light chains secretion, with CD138+ plasma cells more than 50 % according to IHC, with a diffuse type of bone marrow lesion with accumulations of plasma cells. MGUS patients progressed more frequently with more than 20 % CD138+ plasma cells according to IHC, interstitial type and diffuse plasma cells accumulation type of bone marrow lesion, secretion of IgG or two immunoglobulins.Conclusion. The significance of the IHC study in the diagnosis of plasma cell neoplasms was confirmed. Markers associated with the disease progression and chemotherapy resistance in patients with MGUS and MM were identified.